New referencing technique for reservoir oil viscosity estimation (2012)
Reservoir oil viscosity is important in understanding reservoir flow behaviour, facilities design and sizing and in the computation of recovery performance, well' productivity and lift requirements. Direct viscosity measurements are expensive or sometimes unavailable hence empirical correlations are often used for predictions. However, several published correlations are either too simplistic or complex for routine operational use and improved methods continue to receive attention. This study used a semi-theoretical approach to relate reservoir oil viscosity to well-head oil viscosity which can easily be obtained. Results were analyzed statistically and tested with field data obtained from the Niger Delta. The viscosity relation factors developed gave an absolute average relative error (AARE) of 14.1% for undersaturated reservoirs and an AARE of 2.4% for saturated oil reservoirs. It is concluded that measured well-head oil viscosity can be used with good accuracy, as reference liquid instead of dead oil viscosity that has been commonly used for estimating reservoir viscosity.